Permanent Prostate Brachytherapy: The Significance of Postimplant Dosimetry - Lee, W. Robert (MedReviews, LLC, 2004)
Recent developments in imaging science and treatment-planning software allow for accurate postimplant dosimetric assessment in all patients after prostate brachytherapy. This article reviews the available data correlating cancer control and morbidity with dosimetric quantifiers obtained from postimplant dosimetric assessment after prostate brachytherapy. Continued collection of dosimetric data in patients treated with prostate brachytherapy will allow for further refinements in the technique, leading to continued high rates of cure with increasingly lower rates of morbidity.